Analysis of running unlubricated friction pairings under permanent slip with an emphasis on advanced ceramic-steel pairings - Albers, Albert; Meid, Michael (Tribologia - Finnish Journal of Tribology, 2011)
Running clutches under permanent slip offers multiple applications regarding vibration damping or torque distribution in powertrains, for instance. Advanced engineering ceramics show specific benefits in wear behaviour and thermal resistance and are therefore representing an interesting chance for running unlubricated clutches under permanent slip conditions, as well. The emphasis of this analysis is the characterization of the tribological behaviour of the non-oxide ceramic/steel friction pairing SSiC/C45E regarding friction coefficient and wear. As to influencing factors, the sliding speed and contact pressure between the friction surfaces, as well as the specific energy dissipation are varied and analysed. The analysis results of running advanced engineering ceramics under permanent slip are very promising concerning system based friction coefficient level and stability as well as wear behaviour.